Pengaruh Kinerja Perbankan dan Makro Ekonomi terhadap Stabilitas Perbankan pada Bank Pembangunan Daerah di Indonesia tahun 2017-2022 - Andi, Baskoro Qomarul; Heru, Kristanto; Hikmah, Khoirul (Strata Social and Humanities Studies, 2023)
The financial sector depends on banking as a source of the country's economy. Suppose healthy banking conditions and intermediation functions are maintained well. In that case, the money circulation process and monetary policy transmission mechanisms in the economy, mainly through the banking system, will also run well. This research aims to analyze the influence of banking performance and macroeconomic factors on banking stability in Indonesia during 2017-2022. Banking performance factors are LDR, NPL, and CAR, while GDP, inflation, and BI7DRR are macroeconomic factors. This research uses STATA version 17 software, and data is collected using static panel and dynamic panel data. The sample in this study used a purposive sampling technique and obtained 24 regional development banks. This research found that NPL and LDR did not influence banking stability in Indonesia. In contrast, CAR and inflation had a positive and significant impact, and the BI7DRR and GDP variables had a negative and significant influence on banking stability.